2003
DOI: 10.1074/jbc.m209164200
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Protects against 6-Hydroxydopamine-induced Oxidative Stress by Increasing Expression of Heme Oxygenase-1 in a Phosphatidylinositol 3-Kinase-dependent Manner

Abstract: The survival signal elicited by the phosphatidylinositol 3-kinase (PI3K)/Akt1 pathway has been correlated with inactivation of pro-apoptotic proteins and attenuation of the general stress-induced increase in reactive oxygen species (ROS). However, the mechanisms by which this pathway regulates intracellular ROS levels remain largely unexplored. In this study, we demonstrate that nerve growth factor (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
189
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(203 citation statements)
references
References 50 publications
13
189
1
Order By: Relevance
“…3 and 4). The PI3K/Akt pathway was examined as an upstream signaling mechanism of Nrf2 activation, in view of several reports that this pathway is related to HO-1 expression (Martin et al, 2004;Salinas et al, 2003). For example, NGF and herb-derived phenol carnosol enhance HO-1 expression through PI3K/Akt activation in PC12 cells (Martin et al, 2004;Salinas et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 and 4). The PI3K/Akt pathway was examined as an upstream signaling mechanism of Nrf2 activation, in view of several reports that this pathway is related to HO-1 expression (Martin et al, 2004;Salinas et al, 2003). For example, NGF and herb-derived phenol carnosol enhance HO-1 expression through PI3K/Akt activation in PC12 cells (Martin et al, 2004;Salinas et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies show that the PI3K signaling pathway is involved in HO-1 expression (Salinas et al, 2003). Initially, we examined whether adenosine induces Akt phosphorylation, since PI3K phosphorylates Akt (Paez and Sellers, 2003).…”
Section: Adenosine Induces Ho-1 Expression Via Phosphatidylinositol 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators have shown that in vitro exposure to 6-OHDA increases oxidative stress and may lead to apoptosis (Kumar et al, 1995,Park et al, 2002,Soto-Otero et al, 2002,Holtz and O'Malley, 2003,Salinas et al, 2003,Ugarte et al, 2003,Zhuo et al, 2003,Datla et al, 2004,Elkon et al, 2004,Mazzio et al, 2004, and some elements of apoptosis and degeneration occur shortly after in vivo administration of 6-OHDA (Jeon et al, 1995,Joo et al, 1998,Zuch et al, 2000,Kramer and Mytilineou, 2004,Mladenovic et al, 2004. However, little has been reported on in vivo markers of oxidative stress after 6-OHDA administration.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen peroxide also results in neuronal injury through impaired mitochondrial function and increased levels of pro-apoptotic gene products, such as CD95/Fas [56,178,231]. Externalization of membrane PS residues also occurs in neurons during anoxia [38], NO exposure [44], or during the administration of agents that induce the production of ROS, such as 6-hydroxydopamine [194].…”
Section: Alzheimer's Disease In the Aging Populationmentioning
confidence: 99%